Mechanical and Morphological Studies of Sansevieria trifasciata Fiber-Reinforced Polyester Composites with the Addition of SiO2 and B4C - P. Hariprasad; M. Kannan; C. Ramesh; A. Felix Sahayaraj; I. Jenish; Fayaz Hussain; Nidhal Ben Khedher; Attia Boudjemline; V. Suresh (Advances in Materials Science and Engineering)
The impact of SiO2 and B4C on mechanical and morphological studies of Sansevieria trifasciata fiber (STF) reinforced in polyester composites is investigated in this study. STF fibers are reinforced with polyester composites with the addition ceramic fillers such as SiO2 and B4C in various weight fractions to improve tensile, flexural, and impact characteristics. The morphological properties are studied with the help of scanning electron microscopy (SEM). The improved mechanical properties were tensile strength (44.92 MPa), flexural strength (103.58 MPa), and impact strength (27.4 kJ/m2) obtained for 20 wt.% STF fiber and 15 wt.% SiO2 reinforcement with the polyester matrix. The mechanical characteristics of the composites were significantly influenced by increasing SiO2 up to 15 wt.%.